Earls trip - Holiday, Jenny (Romance author) (Kensington Publishing Corp., 2024)
"Even an earl needs his ride-or-dies, and Archibald Fielding-Burton, the Earl of Harcourt, counts himself lucky to have two. The annual trip that Archie takes with his BFFs Simon and Effie holds a sacred spot in their calendars. This year Archie is especially eager to get away until an urgent letter arrives from an old family friend, begging him to help prevent a ruinous scandal. Suddenly the trip has become earls-plus-girls, as Archie's childhood pals, Clementine and Olive Morgan, are rescued en route to Gretna Green. This...complicates matters. The fully grown Clementine, while as frank and refreshing as he remembers, is also different to the wild, windswept girl he knew. This Clem is complex and surprising--and adamantly opposed to marriage. Which, for reasons Archie dare not examine too closely, he finds increasingly vexing. Then Clem makes him an indecent and quite delightful proposal, asking him to show her the pleasures of the marriage bed before she settles into spinsterhood. And what kind of gentleman would he be to refuse a lady?"--